Hungarian Monitoring, 14 October 1990 . [Magyar rádiófigyelő], 1990. október 14 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Summary of events in Jerusalem - Position in European armed forces reductions - Yugoslav domestic developments Domestic Affairs: - Low turn out at repeated self-government elections - German-Hungarian foreign ministers' meeting - George Soros receives human rights prize from American lawyers - József Antall's Dutch schedule Külpolitika: - A jeruzsálemi események összefoglalója - Európai haderőcsökkentés állása - Jugoszláv belpolitikai fejlemények Belpolitika: - Alacsony részvétel a megismételt önkormányzati választásokon - Német-magyar külügyminiszteri találkozó - Soros György emberi jogi díjat kap amerikai jogászoktól - Antall József hollandiai programja